Design and fabrication of cement apply helper / Mohamad Fakhri Mohammad Sukri - Mohammad Sukri, Mohamad Fakhri (2022)
Build a wall is a main process to make a building. Wall is built by assemble the brick together using cement. This process will take a lot of energy and time. The main objective for this project is to solve that two problem. For the first problem is to minimize energy that be using to build the wall. The ideal design for this project is to make sure the product must ha light weight and move smoothly during the work. This Cement Apply Helper machine with an affordable price will make the workers at the site smile and can have a healthy body